2015
DOI: 10.1007/s00415-015-7746-z
|View full text |Cite|
|
Sign up to set email alerts
|

Caregiver burden in amyotrophic lateral sclerosis: a cross-sectional investigation of predictors

Abstract: The objective of the study was to investigate whether cognitive and behavioural impairment in Amyotrophic Lateral Sclerosis (ALS) contributes to caregiver burden, and whether carer burden affects patient outcome. Thirty-three dyads of incident patients with ALS and their primary caregivers (n = 33) completed a series of measures to determine cognitive and behavioural profiles, (patients) and carer burden (carers) to investigate the psychological impact of ALS, and the impact of behavioural change since the ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
64
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 20 publications
9
64
2
3
Order By: Relevance
“…Cui et al [12] found an association between the CBI score and both behavioural (with more extensive impact from disinhibited behaviours) and executive dysfunction, the latter assessed by the FAB in 65 ALS patients. And while the choice of this screening test carries the potential risk of bias due to the frequent need of pro-rating [15] , the same result was also reported by Burke et al [13] on 33 ALS patients studied with a full neuropsychological battery; total behaviour change contributed more than cognition peaking to 31% of caregiver burden, again with more extensive impact from disinhibition. On the other hand, Watermeyer et al [14] reported in 35 patients an association between the Zarit Burden Inventory score with both limb involvement and behavioural problems, but not with executive function.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Cui et al [12] found an association between the CBI score and both behavioural (with more extensive impact from disinhibited behaviours) and executive dysfunction, the latter assessed by the FAB in 65 ALS patients. And while the choice of this screening test carries the potential risk of bias due to the frequent need of pro-rating [15] , the same result was also reported by Burke et al [13] on 33 ALS patients studied with a full neuropsychological battery; total behaviour change contributed more than cognition peaking to 31% of caregiver burden, again with more extensive impact from disinhibition. On the other hand, Watermeyer et al [14] reported in 35 patients an association between the Zarit Burden Inventory score with both limb involvement and behavioural problems, but not with executive function.…”
Section: Discussionsupporting
confidence: 63%
“…The attempt of evaluating the contribution of cognitive deficits to caregiver burden in ALS has been reported only recently [12][13][14] . Cui et al [12] found an association between the CBI score and both behavioural (with more extensive impact from disinhibited behaviours) and executive dysfunction, the latter assessed by the FAB in 65 ALS patients.…”
Section: Discussionmentioning
confidence: 99%
“…The higher the total score (scale of 0–88) the higher the level of perceived burden. Among this cohort the mean global burden score (ZBI) was 27.1 (sd 14.7), and applying a statistically derived cut-off score of ≥24 [13, 26], (Appendix 1, Table 1) indicates that 52 % of this caregiver cohort were in the ‘high burden’ category at their baseline interview.…”
Section: Resultsmentioning
confidence: 99%
“…Patient physical, cognitive and behavioural impairments can contribute substantially to the psychological and physical morbidity of the caregiver and affect caregiver burden in ALS [13, 14]. Effects on the caregiver’s health can be moderated by individual differences in resources and vulnerabilities, socioeconomic position, prior health status, and level of social support [15].…”
Section: Introductionmentioning
confidence: 99%
“…Family carers in ALS encounter caregiver burden (3,4) and caregiver burden can have an adverse effect on their wellbeing (5). Caregiver burden in ALS increases with disease duration (6) and is higher among those who care for patients who have behavioural impairment (7).…”
Section: Introductionmentioning
confidence: 99%